Private higher education : an international bibliography - Maldonado, Alma; Cao, Yingxia; Altbach, Philip G.; Levy, Daniel C.; Zhu, Hong (Emerald Publishing Limited : Information Age Publishing, 2004)
This research project has been supported by the Ford Foundation, the Lynch School of Education at Boston College, and the Program of Research on Private Higher Education at the University at Albany.
Keywords: Education, Higher -- Bibliography.; Private universities and colleges -- Bibliography.; elektronické knihy; Bibliographies.; Education -- Schools -- Levels -- Higher.; Higher education, tertiary education.; electronic books